The erosion of tells: a note - Davidson , Donald A. (Journal of Greek Archaeology, 2024)
The accumulation of sediments is an inevitable consequence of human occupation at a specific locality. A wide range of results is possible with the most spectacular being the formation of mounds or tells which consist primarily of unconsolidated sediments, usually calcareous. Tells are primarily associated with the Middle East extending from the eastern Mediterranean to modern Turkey, Iran and Iraq. Lloyd was an early writer to describe their nature and distribution and he attributed their formation primarily to the collapse of mudbrick houses, an opinion still widely accepted. Tells are distinctive landscape features, often standing 10 to 15m above the local plain.